ATRIAL FIBRILLATION COMBINED WITH DIABETES MELLITUS. POSSIBILITIES OF USING RIVAROXABAN - Alexey D. Ehrlich («REMEDIUM GROUP» Ltd., 2018)
The presented material summarizes the main clinical and theoretical data on the peculiarities of atrial fibrillation (AP) flow in combination with diabetes mellitus (DM). This combination, although associated with a lower age than in patients without diabetes, is associated with a higher risk of stroke and systemic embolism and other adverse complications. The material presents the data of the rocket-AF randomized trial subanalysis on the peculiarities of the use of oral anticoagulant - a direct inhibitor of Xa-factor Rivaroxaban in patients with non-valve AF in combination with DM. Comparative efficacy and safety of Rivaroxaban in patients with diabetes were comparable to those in patients without diabetes. Rivaroxaban in patients with diabetes was associated with lower vascular death rates than warfarin. The results of the randomized trial are largely confirmed in several observational studies that reflect actual clinical practice. Thus, it can be affirmed that Rivaroxaban is not only the most commonly used direct oral anticoagulant in russian practice, but can also be widely used in patients with non-valve AF and diabetes to prevent strokes and systemic embolisms.